Drug testing in sport: The attitudes and experiences of elite athletes - Dunn, M.; Thomas, J. O.; Swift, W.; Burns, L.; Mattick, R. P. (International Journal of Drug Policy, 2010)
Background: This study aimed to investigate, among a sample of elite Australian athletes, the extent to which this group supports drug testing as a deterrent to drug use. Method: Data was collected from a convenience sample of (n = 974) elite Australian athletes who self-completed a questionnaire, and semi-structured telephone surveys with key experts. Results: The athletes surveyed endorsed testing for banned substances as an effective way of deterring drug use; believed that the current punishments for being caught using a banned substance was of the appropriate severity; and indicated that there should be separate policies regarding illicit drug (ID) and performance-enhancing drug (PED) use. Conclusion: A large proportion of elite athletes in Australia endorse drug testing as an effective means of deterring drug use. They perceive a difference between being detected using a PED and an ID and believe that penalties should reflect this difference. Future research may wish to investigate attitudes towards newer methods employed to detection drug use.